Kulturnopolitične in jezikovnopolitične razmere na Slovenskem ob koncu prve svetovne vojne - Štuhec, Miran (Studia Historica Slovenica, 2020)
After the World War I two things happened on the patriotic-national field: the interruption of currents, which were for several centuries including the Slovenian cultural and spiritual space in Habsburg monarchy, and unproductive competition of political parties, which was in the time od important questions about cultural and political positioning especially dangerous. The intensive search within the territorially-political provisional arrangement SHS and later Kingdom of SHS was the continuation of pre-war processes; at the same time we can ascertain that the culturally-political dynamics of the 19th Century sharpened significantly. The consequences included many contradictions, not clearly enough defined purposes, calculating and searching for short-term goals.
Keywords: cultural authonomy; culture; jezik; Kraljevina SHS; kulturna avtonomija; kulturna zgodovina; language; multilingualism; narodnostno vprašanje; party politics; politične razmere; politične stranke; Slovenija; Svetovna vojna 1914-1918; šolstvo; večjezičnost